Reflection of Brahui Culture in Brahui Modern Prose - Dinakhel, Dr. Muhammad Ali (Al-Burz, 2020)
According to a proverbial saying of Mattew Arnold, literature is the reflection of society. Following this idea it is true that the best reflection of a culture and society is found in the literature of that very community. Writers reflect culture in their writings because they can’t live without being influenced by the environment in which they live. Environment has its influence upon writers and that is why a writer or poet directly or indirectly describes his environment and culture. As compare to poetry, culture is visibly seen in prose. Same is the case of the reflection of Brahui culture in its prose. We easily know about the main cultural tenets of Brahui people through their literature. Their life-style, customs, food, education, professions, religion etc. are found in the prose of Brahui Literature. Modern genres in Brahui Prose, like novel, short story, drama etc. are the main sources of Brahui Culture. This article attempts to analyse modern genres of prose like novel, drama, short story and so on in Brahui language to discover and point out main features of Brahui Culture. Key Words: Brahui, Culture, Balochistan, Literature, Prose